Filmowe kłopoty z Prusem. O "Faraonie" Jerzego Kawalerowicza = Film troubles with Prus - about "Pharaoh" by Jerzy Kawalerowicz - Blech, Roksana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article we want to demonstrate that Boleslaw Prus' prose is hardly translatable into the film medium, that it is a difficult task and a challenge for a director. The subject of our analysis is the 1966 film by Jerzy Kawalerowicz. I am convinced that his directing work: the use of colour and music,the set design and construction, as well as the reliable representation of the reality of ancient Egyptdeserve recognition.
Keywords: Prus, Bolesław(1847-1912). Faraon; adaptacja filmowa